Potencial benefit of erythropoietin to prevent iron induced cardiovascular disease - Fernandez Delias, María Florencia (2019)
The prevalence of iron overload cardiomyopathy is increasing. There is growing evidence that high iron levels are a risk factor for cardiovascular disease because can cause constriction of blood vessels.The aim was to study the erythropoietin (EPO) role to prevent iron induced cardiovascular disease studying key importer proteins in the heart in an animal model of iron overload and EPO. CF1 mice (25±5g; 3 months) were divided into groups (n=4/group):1)Iron-adequate (IA); 2)Iron-overload (IO) (iron saccharate; days 0,4,8,12 ip;1800mg/kg); 3)EPO (days17,18,19) ip; 20000UI/kg); 4)Iron-overload+EPO (IO+EPO). Immunohistochemistry:anti-DMT1(divalent metal transporter1) and ZIP14(Zrt-Irt-like Protein14).Perl´s staining .Iron levels were measured by FeRcolor.The Protocol was approved by the CICUAE,UNS. Heart DMT1 expression was evident in IA and EPO groups and it was scarce in IO and IO+EPO conditions. However heart ZIP14 expression was evident in all conditions demonstrating that it´s expression not depends of the ?iron signal?. The decrease in the DMT1 expression in IO state would suggest a protective mechanism against iron excess in heart tissue, being the ?iron signal? the predominant signal to decrease the biometal uptake. Iron levels in heart shows significant increase in IO respect to IA condition. Interestingly, the iron levels in IO+EPO were significantly decreased respect to IO. Consequently, abundant hemosiderin was observed in IO condition and it was scarce in IO+EPO group. Hemosiderin was absent in IA and EPO conditions. Our data showed that Iron uptake in IO would not depend on the expression of DMT1 either ZIP14. Thus, we can conclude that erythropoietin the ?EPO signal? in high iron levels may have a direct positive effect on the heart. In conclusion, the interplay between EPO and key proteins of the iron cycle, such as DMT1 and ZIP14 may help to better understand the mechanisms involved in iron and erythropoiesis regulation in heart tissue.